2023
DOI: 10.1039/d2fo02659g
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium bifidum FJSWX19M5 alleviated 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced chronic colitis by mitigating gut barrier injury and increasing regulatory T cells

Abstract: Probiotics have been evaluated as alternative approaches to preventing relapse of Crohn's disease (CD). Previously, we observed strain-specific anti-inflammatory properties of Bifidobacterium bifidum in 2,4,6-trinitrobenzene sulfonic acid (TNBS) acute colitis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…125 The study conducted by Qu and colleagues provided evidence that the administration of FJSWX19M5 resulted in the augmentation of Tregs and had a role in the recovery of the intestinal barrier. 69 This observation implies that FJSWX19M5 could possess immunomodulatory characteristics that contribute to regulating the immune response inside the gastrointestinal tract. Additionally, it was shown that the co-cultivation of B. bifidum strains with anticolitis capabilities induced an elevation in the expression of the cytokine that inhibits inflammation IL-10 and a decreased ratio of proinflammatory cytokines (IL-22/IL-10 and IL-17/IL-10) as compared to nonprotective strains.…”
Section: Effects Of Probiotics On T Cells In Ucmentioning
confidence: 98%
See 4 more Smart Citations
“…125 The study conducted by Qu and colleagues provided evidence that the administration of FJSWX19M5 resulted in the augmentation of Tregs and had a role in the recovery of the intestinal barrier. 69 This observation implies that FJSWX19M5 could possess immunomodulatory characteristics that contribute to regulating the immune response inside the gastrointestinal tract. Additionally, it was shown that the co-cultivation of B. bifidum strains with anticolitis capabilities induced an elevation in the expression of the cytokine that inhibits inflammation IL-10 and a decreased ratio of proinflammatory cytokines (IL-22/IL-10 and IL-17/IL-10) as compared to nonprotective strains.…”
Section: Effects Of Probiotics On T Cells In Ucmentioning
confidence: 98%
“…This implies that the advantageous strains have the potential to regulate the immune response in a manner that decreases inflammation associated with colitis. 69 Furthermore, the findings of Qu and colleagues showed that the injection of heat-killed FJSWX19M5 positively impacted symptoms associated with colitis. This suggests that the therapeutic effects of this treatment may not only depend on the presence of live bacteria.…”
Section: Effects Of Probiotics On T Cells In Ucmentioning
confidence: 99%
See 3 more Smart Citations